The Effect of Different Weight Status on Social-Emotional Skills of Adolescents - Aydos, Sebahat; Akyol, Aysel Köksal (International Journal of Child Health and Nutrition, 2018)
Obesity, which can occur due to numerous causes especially from genetics to nutrition disorders, is a major problem not only for adults but also for children. Childhood obesity causes acute and chronic physical problems in children, but physical effects of obesity, as well as psycho-social effects on children, is a substantial issue. This study was conducted to analyze the effect of different weight status on social-emotional skills of adolescents. The research group comprised 189 female and 194 male of 383 total children who were still on the 6th, 7th and 8th grades at the schools. The General Information Form prepared by the researchers and the "Social Emotional Learning Skills Scale" developed by Kabakçı and Korkut Owen were utilized as data collection tools. Two-way analysis of variance and Tukey tests were performed for the analysis of the data. As a result of the study conducted, it is observed that social-emotional learning skills of adolescents aged 12-14 years are significantly different according to their weight status and gender. It has been found that the communication and social-emotional skills of overweight adolescents are significantly lower than normal adolescents and that obese adolescents have significantly lower communication, problem-solving, coping with stress, self-worth increasing and social-emotional learning skills than thin, normal and overweight adolescents. It is observed that male adolescents have significantly lower communication, problem-solving, stress coping and social-emotional learning skills than female adolescents.